1990
DOI: 10.1111/j.1547-5069.1990.tb00166.x
|View full text |Cite
|
Sign up to set email alerts
|

The Tradition of Toughness: A Study of Nonprofessional Nursing Care in Psychiatric Settings

Abstract: Violence is a significant problem in psychiatric settings; however, nursing research that identifies organizational influences related to violent patient behavior is rare. This paper reports on an exploratory study conducted on the psychiatric units of a metropolitan public hospital. The key concept generated by the data was the "tradition of toughness." Within this psychiatric setting, "control" of patient behavior was emphasized resulting in norms and roles that operationalized the theory. The norms were (a)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
88
2
5

Year Published

1993
1993
2012
2012

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(96 citation statements)
references
References 15 publications
1
88
2
5
Order By: Relevance
“…Giroux (1983) has noted that youngsters may be expected to resist institutional definitions of their lives and attempt to assert a sense of self in institutions which pressure them to do otherwise. The emphasis on rules and social control, which is the norm in psychiatric institutions for both children and adults (Morrison, 1990;Rivkin & Wolfe, 1985), exerts precisely this kind of pressure.…”
Section: Discussionmentioning
confidence: 98%
“…Giroux (1983) has noted that youngsters may be expected to resist institutional definitions of their lives and attempt to assert a sense of self in institutions which pressure them to do otherwise. The emphasis on rules and social control, which is the norm in psychiatric institutions for both children and adults (Morrison, 1990;Rivkin & Wolfe, 1985), exerts precisely this kind of pressure.…”
Section: Discussionmentioning
confidence: 98%
“…The philosophy of the unit, in particular a medical model orientation, was found to be related to the use of restraint as a suitable means to maintain control (Morrison, 1990a). Similarly, Australian nurses reported that policies and procedures related to managing aggression were not always easily accessible, and that there was a need for a more structured approach to assessing risks for client aggression (Delaney et al, 2001).…”
Section: Nurse Practice Environmentmentioning
confidence: 96%
“…Limited research has been conducted on the nursing practice environment of inpatient psychiatric nurses, particularly in the United States where existing studies are limited to dissertations (Heeren, 1991;Kearney, 1995;Mohr, 1995); a study related to assault against psychiatric nurses (Poster & Ryan, 1994); and studies about the organization of a unit (Morrison, 1990a(Morrison, , 1990b(Morrison, , 1998. The extant literature related to inpatient psychiatric nurses was conducted in Australia and New Zealand (Berg & Hallberg, 2000;Cleary, 2004;Cleary & Edwards, 1999;Delaney, Clearly, Jordan, & Horsfall, 2001;Farrell & Dares, 1999;Fourie, McDonald, Connor, & Barlett, 2005;Happell, Martin, & Pinikahana, 2003;O'Brien & Cole, 2004;Taylor & Barling, 2004), Canada (Robinson, Clements, & Land, 2003), England (Callaghan, 1991;Fagin, Brown, Bartlett, Leary, & Carson, 1995;Fagin et al, 1996;Hall, 2004;Higgins, Hurst, & Wistow, 1999;Mistral, Hall, & McKee, 2002;Sammut, 1997;Sullivan, 1993;Whittington, 2002;Whittington & Wykes, 1992), Norway (Severinsson & Hummelvoll, 2001), Sweden (Severinsson & Hallberg, 1998), Japan (Ito, Eisen, Sederer, Yamada, & Tachimori, 2001), and a combination of two or more of the above countries (Melchior, Bours, Schmitz, & Wittich, 1997;Thomsen, Arnetz, Nolan, Soares, & Dallender, 1999).…”
Section: Nurse Practice Environmentmentioning
confidence: 97%
“…Alternatively, the early impact of training on aggression rates may be a 'Hawthorne Effect', due to novelty, and wear off in the longer term. The most negative interpretation is that training in the management of aggression makes staff more confident and more likely to confront patients, elicit a violent response and use the manual restraint techniques they have been taught (Morrison 1990). It may be that such a response only occurs with more superficial training, thus the rise in violence following update rather than 5-day courses.…”
Section: Discussionmentioning
confidence: 99%